Multimodality imaging for transcatheter aortic valve replacement - Berman, Daniel S.; Leipsic, Jonathon; Min, James K. (Springer London, 2014)
Over the last decade, remarkable innovations in transcatheter technologies have led to the rapid development of minimally invasive therapies that have challenged conventional treatment.  Amongst these, none is as remarkable as transcatheter aortic valve replacement (TAVR).  An archetype of "bench-to-bedside" medicine, the origins of TAVR spanned the expertise and vision of clinicians, engineers, researchers and imagers. With increasing numbers of TAVR procedures and large-scale trials demonstrating an unparalleled reduction in mortality for inoperable patients with severe aortic valvular disease, the theme underpinning the foundation of TAVR - that of a multidisciplinary approach to its development - persists in its practice. This approach brings together a diverse group of experts to optimize patient outcomes and this extends to the convergence of different types of imaging specialists and modalities to support preparation for and performance and follow-up of TAVR. Multimodality Imaging for Transcatheter Aortic Valve Replacement assembles the very best authorities in the field to create the ultimate resource to address the imaging needs associated with TAVR. It provides the reader with a comprehensive understanding of the pathophysiology of aortic stenosis, the evidence supporting the use of TAVR, and an integrated approach to the indications, procedural aspects and pitfalls of imaging in TAVR. The reader will also gain an insight into which tests are optimal in specific situations and a step-wise method to harvest all the essential information provided with each modality. Thus, this book represents a key resource for all working in the field whether they be in training or practicing physicians, cardiac researchers, cardiac imagers, interventionalists, clinical cardiologists, cardiac surgeons, or any medical professional involved in the management of these patients.